Antivirals for Idiopathic Sudden Sensorineural Hearing Loss. (2nd September 2014) - Awad, Zaid; Huins, Charlie; Pothier, David D.
Abstract : Objectives: Determine the effectiveness and side effect profile of antivirals in the treatment of idiopathic sudden sensorineural hearing loss (ISSHL). Methods: We systematically searched the Cochrane Ear, Nose and Throat Disorders Group Trials Register, the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library 2012, Issue 5), PubMed, EMBASE, CINAHL, and other databases to June 12, 2012. Reference lists of identified studies for further trials were also scanned. Selection criteria: Randomized controlled trials (RCTs) comparing different antivirals versus placebo (both with or without other treatment). Two authors independently extracted data. Meta‐analysis was considered inappropriate and ultimately not possible due to differing treatment protocols and differing inclusion criteria and outcome measures between studies. Results: Four RCTs (257 participants) were identified. Two trials compared the addition of intravenous acyclovir with a steroid (prednisolone). Neither demonstrated any hearing improvement with ISSHL. Another showed no benefit with the addition of valacyclovir to prednisolone on hearing outcome. Comparing intravenous acyclovir plus hydrocortisone with hydrocortisone alone, the final trial did not show any statistically significant difference between groups. Even though no meta‐analysis was possible, evidence from 4 RCTs has demonstrated no statistically significant advantage in the use of antivirals in the treatment of ISSHL. Conclusions: There is no evidence to support the use of antiviral drugs in the treatment of ISSHL. Further randomized controlled trials are needed for adequate meta‐analysis to be performed to reach definitive conclusions. A uniform definition of ISSHL should also be established, together with what constitutes adequate recovery.